How Dengue Virus Circumvents Innate Immunity - Kao, Yu-Ting; Lai, Michael M. C.; Yu, Chia-Yi (Frontiers in Immunology, 2018)
In the battle between a virus and its host, innate immunity serves as the first line of defense protecting the host against pathogens. The antiviral actions start with the recognition of pathogen-associated molecular patterns derived from the virus, then ultimately turning on particular transcription factors to generate antiviral interferons (IFNs) or proinflammatory cytokines via fine-tuned signaling cascades. With dengue virus (DENV) infection, its viral RNA is recognized by the host RNA sensors, mainly retinoic acid inducible gene-I (RIG-I)-like receptors (RLRs) and toll-like receptors. DENV infection also activates the cyclic GMP-AMP synthase–stimulator of interferon genes (cGAS–STING)-mediated DNA-sensing pathway despite the absence of a DNA stage in the DENV lifecycle. In the last decade, DENV has been considered a weak IFN-inducing pathogen with the evidence that DENV has evolved multiple strategies antagonizing the host IFN system. DENV passively escapes from innate immunity surveillance and also actively subverts the innate immune system at multiple steps. DENV targets both RNA-triggered RLRmitochondrial antiviral signaling protein (RLRMAVS) and DNA-triggered cGASSTING signaling to reduce IFN production in infected cells. It also blocks IFN action by inhibiting IFN regulatory factor- and signal transducer and activator of transcription-mediated signaling. This review explores the current understanding of how DENV escapes the control of the innate immune system by modifying viral RNA and viral protein and by post-translational modification of cellular factors. The roles of the DNA-sensing pathway in DENV infection, and how mitochondrial dynamics participates in innate immunity are also discussed.